Pengaruh Penerapan Kurikulum 2013 dan Kurikulum Merdeka terhadap Peningkatan Kompetensi Profesional Guru PAI Tingkat Sekolah Dasar - Mawardhani, Kartika Azaza; Mutiara, Diah (FONDATIA, 2025)
One of the obstacles faced by a teacher is changes in the educational curriculum which requires a teacher to adapt to the current curriculum. This definitely has an impact on a teacher's professional competence. The aim of this research is to determine the extent of the influence of the 2013 Curriculum and the Merdeka Curriculum on Increasing the Professional Competence of Islamic Religious Education Teachers.This research is quantitative research using application assistance SPSS 25.0. This research was conducted at an elementary school in Pasar Minggu District. This research sample was taken using techniques Probability Sampling that is Random Sampling a total of 52 samples of Islamic Religious Education Teachers. The research instrument was distributed via Goggle Form. The research results show that There is an influence of the Implementation of the 2013 Curriculum and the Merdeka Curriculum on Increasing the Professional Competence of Islamic Religious Education Teachers at the Elementary School Level in Pasar Minggu District.